A review on primary synthesis and secondary treatment of aluminium matrix composites. Issue 1 (1st January 2020) - Orhadahwe, T. A.; Ajide, O. O.; Adeleke, A. A.; Ikubanni, P. P.
Abstract: In this paper, the primary synthesis and secondary treatment of Aluminium matrix composites (AMCs) has been reviewed. The renewed quest for component materials with high strength-to-weight ratio, unusual and superlative combination of properties for applications in automotive, aerospace, marine and warfare armoury manufacturing industries has increased the versatility potential of aluminium alloy-based composites. Several categories (synthetic and agro-based ceramics) of reinforcement materials for aluminium composite are discussed. The manufacturing/fabrication techniques which could be solid phase (powder metallurgy and rapid prototyping or 3 D printing method) or liquid phase (casting and pressure infiltration) methods are discussed in this review work. Secondary treatment such as heat treatment, forging and other thermomechanical treatments which improves the properties of as-synthesized composites are also discussed. A review synopsis of recent studies provides opportunity for concise but a more robust understanding of potential benefits and detrimental effects associated with the use of various primary synthesis routes and secondary treatment for manufacturing of ceramic reinforced AMCs. Despite the laudable research efforts that have been made towards development and enhancement of the properties of AMCs, this review work revealed that literature is very sparse on synergetic adoption of multi-synthesis route and multi-approach secondary treatment for producing AMCs. Sequel to the aforementioned unexplored research concept, some lacunae are identified and suggested for further elaborations and study.